Hermit crabs from Brazil. Family Paguridae (Crustacea: Decapoda: Paguroidea): Genus Pagurus - Nucci, Paulo Ricardo; de Melo, G. A. S. T (Zootaxa, 2007)
In Brazil, the hermit crab family Paguridae is represented by 11 genera, of which the genus Pagurus is the most speciose, with seven species that occur from the intertidal zone to shallow waters and one from deeper regions. In this paper we present the diagnosis, distribution and some remarks on each species of the genus Pagurus known from Brazil.